Exploring microplastic pollution in the pristine Ghar-e-Tangi cave: First evidence from Pakistan’s subterranean ecosystem - Luqman Muhammad; Awan Umer F.; Arooj Fariha; Khalid Muhammad Awais; Afzaal Muhammad; Shahid Tahreem; Niazi Aliza; Yang Hsi-Hsien; Khan Shaukat Hayat (Archives of Biological Sciences)
Microplastics (MPs) are a pervasive environmental pollutant, yet their presence in subterranean environments, particularly in remote locations, remains understudied. This study quantifies the abundance, distribution, and characteristics of MPs in the sediments of Ghar-e-Tangi, an isolated cave in Balochistan, Pakistan, and explores their potential input pathways. Triplicate sediment samples were collected from three distinct sites along a gradient from entrance to deeper sections. MPs were extracted and analyzed for their number, color, size, and shape using microscopy, while MPs ≥ 1 mm were characterized via Fourier transform infrared spectroscopy (FTIR). Significant differences were observed in the distribution of MP by shape (P=0.004), color (P=0.002), and size (P=0.005), as well as across the sites (P=0.001–0.041). MP abundance decreased significantly from the entrance to deeper sections (Site A=99 MPs/kg, Site B=49 MPs/kg, Site C=37 MPs/kg, P=0.001). Transparent MPs were predominant (38.4%, 23.67}10.97), along with eight identified colors. Of the five shapes identified, fragments were the most prevalent (36.8%, 22.67}11.72). MPs measuring >3-5 mm constituted the largest proportion (45.4%, 28.0}14.42). The observed gradient suggests surface runoff and atmospheric deposition as primary input pathways. These findings align with global studies, highlighting the pervasive nature of MPs, even in remote environments such as the Ghar-e-Tangi cave.